Interpretation of Platelet Histograms and Its Correlation with Peripheral Smear in Data Showing Thrombocytopenia - Shinde, Aparna; Modi, Alisha; Patil, Amruta (International Journal of Integrated Health Sciences, 2024)
Objective: To analyze the significance of platelet histograms and peripheral smears in understanding thrombocytopenia and compare them for the incidence of pseudothrombocytopenia.Methods: This prospective study was conducted in the Department of Pathology at a tertiary care medical institute. The study included 200 cases of thrombocytopenia. Platelet parameters (PCT, PDW, MPV) were obtained using an autoanalyzer, and peripheral smears were examined manually. Thrombocytopenia cases were classified into hyper-destructive, hypo-productive, and abnormal pooling categories based on etiology and platelet histogram patterns. The incidence of pseudothrombocytopenia was also compared. A P value of less than 0.05 was considered statistically significant. Results: The gender distribution showed a male preponderance (56% male, 44% female). The mean age of the patients was 26.8 years. The study found hyper-destructive thrombocytopenia to be the most common type, with viral fever, sepsis, and malaria being the common etiologies for this type of thrombocytopenia. Histogram analysis revealed distinct patterns for different types of thrombocytopenia. The study also noted a higher incidence of pseudothrombocytopenia in automated analysis compared to manual methods, with a statistically significant difference.Conclusion: Platelet histograms combined with peripheral smear analysis provide crucial information about the etiology and nature of thrombocytopenia. This integrated approach enhances diagnostic accuracy and aid in effective patient management.